Pectin and xyloglucan influence the attachment of Salmonella enterica and Listeria monocytogenes to bacterial cellulose-derived plant cell wall models - Tan, M.; Rahman, S.; Dykes, Gary (2016)
Minimally processed fresh produce has been implicated as a major source of foodborne microbial pathogens globally. These pathogens must attach to the produce in order to be transmitted. Cut surfaces of produce that expose cell walls are particularly vulnerable. Little is known about the roles that different structural components (cellulose, pectin, and xyloglucan) of plant cell walls play in the attachment of foodborne bacterial pathogens. Using bacterial cellulose-derived plant cell wall models, we showed that the presence of pectin alone or xyloglucan alone affected the attachment of three Salmonella enterica strains (Salmonella enterica subsp. enterica serovar Enteritidis ATCC 13076, Salmonella enterica subsp. enterica serovar Typhimurium ATCC 14028, and Salmonella enterica subsp. indica M4) and Listeria monocytogenes ATCC 7644. In addition, we showed that this effect was modulated in the presence of both polysaccharides. Assays using pairwise combinations of S. Typhimurium ATCC 14028 and L. monocytogenes ATCC 7644 showed that bacterial attachment to all plant cell wall models was dependent on the characteristics of the individual bacterial strains and was not directly proportional to the initial concentration of the bacterial inoculum. This work showed that bacterial attachment was not determined directly by the plant cell wall model or bacterial physicochemical properties. We suggest that attachment of the Salmonella strains may be influenced by the effects of these polysaccharides on physical and structural properties of the plant cell wall model. Our findings improve the understanding of how Salmonella enterica and Listeria monocytogenes attach to plant cell walls, which may facilitate the development of better ways to prevent the attachment of these pathogens to such surfaces.